Syntheses, crystal structures and thermal properties of catena-poly[cadmium(II)-di-μ-bromido-μ-pyridazine-κ2N1:N2] and catena-poly[cadmium(II)-di-μ-iodido-μ-pyridazine-κ2N1:N2] - Christian Näther; Inke Jess (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The reactions of cadmium bromide and cadmium iodide with pyridazine (C4H4N2) in ethanol under solvothermal conditions led to the formation of crystals of [CdBr2(pyridazine)]n (1) and [CdI2(pyridazine)]n (2), which were characterized by single-crystal X-ray diffraction. The asymmetric units of both compounds consist of a cadmium cation located on the intersection point of a twofold screw axis and a mirror plane (2/m), a halide anion that is located on a mirror plane and a pyridazine ligand, with all atoms occupying Wyckoff position 4e (mm2). These compounds are isotypic and consist of cadmium cations that are octahedrally coordinated by four halide anions and two pyridazine ligands and are linked into [100] chains by pairs of μ-1,1-bridging halide anions and bridging pyridazine ligands. In the crystals, the pyridazine ligands of neighboring chains are stacked onto each other, indicating π–π interactions. Larger amounts of pure samples can also be obtained by stirring at room-temperature, as proven by powder X-ray diffraction. Measurements using thermogravimetry and differential thermoanalysis (TG-DTA) reveal that upon heating all the pyridiazine ligands are removed in one step, which leads to the formation of CdBr2 or CdI2.